Research progress on the factors influencing the bonding effect of universal adhesives on tooth tissues - XU Yili (Editorial Department of Journal of Prevention and Treatment for Stomatological Diseases, 2022)
Universal adhesives have been widely used in dentistry due to their easy application process and wide range of applications. In the literature, the etching modes of universal adhesives, coating methods of universal adhesives, pretreatment of adhesive, and other factors were reported to have an impact on the bonding performance of universal adhesives. This review focused on the factors affecting the bonding performance of universal adhesives and aimed to provide evidence-based recommendations for clinical practice. Current research suggests that the etch-and-rinse mode can achieve a better adhesive strength of enamel and that the etch-and-rinse mode and the self-etch mode exhibit a similar adhesive performance in bonding dentin. The bond strength would be improved by prolonging the application time, applying a double layer of adhesives, and wetting enamel and dentin with water or ethanol before adhesive procedures. Chlorohexidine (0.2%) and metal nanoparticles can inhibit matrix metalloproteinases (MMPs) and improve the long-term bond strength of dentin. Finally, universal adhesives have excellent stability and saliva pollution resistance, although they lack blood pollution resistance. In the clinic, dentists should pay attention to the etching modes of universal adhesives, coating methods of universal adhesives, pretreatment of adhesive, and other factors that may affect the effect strength. universal adhesives will be improved in bonding strength of enamel in self-etch mode and bonding performance in demineralized dentals around caries.